Evaluating the Dynamic Elastic Modulus of Concrete Using Shear-Wave Velocity Measurements. (24th July 2017) - Lee, Byung Jae; Kee, Seong-Hoon; Oh, Taekeun; Kim, Yun-Yong
Abstract : The objectives of this study are to investigate the relationship between static and dynamic elastic moduli determined using shear-wave velocity measurements and to demonstrate the practical potential of the shear-wave velocity method for in situ dynamic modulus evaluation. Three hundred 150 by 300 mm concrete cylinders were prepared from three different mixtures with target compressive strengths of 30, 35, and 40 MPa. Static and dynamic tests were performed at 4, 7, 14, and 28 days to evaluate the compressive strength and the static and dynamic moduli of the cylinders. The results obtained from the shear-wave velocity measurements were compared with dynamic moduli obtained from standard test methods (P-wave velocity measurements according to ASTM C597/C597M-16 and fundamental longitudinal and transverse resonance tests according to ASTM C215-14). The shear-wave velocity measured from cylinders showed excellent repeatability with a coefficient of variation (COV) less than 1%, which is as good as that of the standard test methods. The relationship between the dynamic elastic modulus based on shear-wave velocity and the chord elastic modulus according to ASTM C469/C469M was established. Furthermore, the best-fit line for the shear-wave velocity was also demonstrated to be effective for estimating compressive strength using an empirical relationship between compressive strength and static elastic modulus.